Differential effects of schooling and cognitive and non‐cognitive skills on labour market outcomes: The case of the garment industry in Ethiopia. (31st December 2021) - Yamada, Shoko; Otchia, Christian S.
Abstract: The paper contributes to the discussion of the effects of educational attainment and skills on labour market outcomes, especially in a fast‐growing economy. The data are derived through the authors' unique skills assessment of 591 workers at 19 foreign‐invested garment‐production companies in Ethiopia, which allows for the analysis of the impact of cognitive, non‐cognitive, and practical skills separately from that of years of schooling. Instead of using the total score of a written test as a proxy for skills, we examine the composition of skills more closely. Our findings indicate that the schooling record is a significant determinant of wage, although the level of basic cognitive skills does not necessarily correspond to participants' educational backgrounds. We also find that the non‐cognitive skills needed to perform tasks accurately and with confidence are important for both written test performance and higher wages. Employers reward people with practical skills and knowledge directly related to work, although our findings suggest that overall cognitive capacities are developed holistically from a combination of different types of skills such as mathematical, reading, and analytical. The study highlights how developing economies face different skills assessment challenges than developed economies.